Evaluation of Rebar Waste Rate Calculation Model Utilizing BIM Function: High Rise Building Case Study - Ryan Faza; Rama Adjie Darmawan; Danny Triputra Setiamanah (Aptisi Transactions On Technopreneurship (ATT), 2023)
The process that has the potential to generate construction waste is a construction operational process so that in this process it is necessary to make efforts to carry out waste control in real-time as a form of effort by the construction industry to play a role in suppressing waste production. BIM is one of the supporting tools for project productivity whose function can be used to evaluate the level of construction waste, especially rebar waste which is one of the source materials for construction waste. The purpose of this study is to test the modeling of the calculation of the rebar waste rate utilizing the function of the BIM so that it can be used as an alternative tool for evaluating the level of waste in real-time. The calculation modeling obtained from previous research was successfully tested on a case study of a high-rise building project and obtained the rebar waste rate at a certain time in accordance with the progress of work in the project site. From this research, it can be concluded that the calculation modeling can be carried out on high-rise building projects.